Control and trust as organising principles for international joint ventures. (20th October 2010) - Mohr, Alexander T.; Puck, Jonas
Executives managing an international joint venture (IJV) make (explicit or implicit) assumptions about the level of their respective partner firm's tendency to act opportunistically. Based on this assumption a tendency towards either control or trust characterises executives' approach towards managing the IJV. Trust and control are seen as distinct organising principles that partner firms apply in varying degrees when managing IJV relationships. This article empirically investigates the existence and nature of these two principles using data from 110 representatives of German-Chinese IJVs. The findings of the study show that the two organising principles can be distinguished empirically and that they are associated with differences in interaction patterns, partner compatibility, as well as IJV performance. The article suggests that the concept of organising principles is useful for structuring and making sense of the often ambiguous and disparate findings in existing IJV research.